Cell‐Based Identification of New IDO1 Modulator Chemotypes. (24th March 2021) - Hennes, Elisabeth; Lampe, Philipp; Dötsch, Lara; Bruning, Nora; Pulvermacher, Lisa‐Marie; Sievers, Sonja; Ziegler, Slava; Waldmann, Herbert
Abstract: The immunoregulatory enzyme indoleamine‐2, 3‐dioxygenase (IDO1) strengthens cancer immune escape, and inhibition of IDO1 by means of new chemotypes and mechanisms of action is considered a promising opportunity for IDO1 inhibitor discovery. IDO1 is a cofactor‐binding, redox‐sensitive protein, which calls for monitoring of IDO1 activity in its native cellular environment. We developed a new, robust fluorescence‐based assay amenable to high throughput, which detects kynurenine in cells. Screening of a ca. 150 000‐member compound library discovered unprecedented, potent IDO1 modulators with different mechanisms of action, including direct IDO1 inhibitors, regulators of IDO1 expression, and inhibitors of heme synthesis. Three IDO1‐modulator chemotypes were identified that bind to apo‐IDO1 and compete with the heme cofactor. Our new cell‐based technology opens up novel opportunities for medicinal chemistry programs in immuno‐oncology. Abstract : Heme‐competitive indoleamine‐2, 3‐dioxygenase (IDO1) small‐molecule modulators are under‐represented as heme displacement is delayed in in vitro assays. This limitation can be overcome by cell‐based screening as employed in this study, which revealed novel chemotypes that potently inhibit IDO1 activity and kynurenine production by competing with heme.